Zur geomorphologischen Höhenstufung der Sierra Nevada Spaniens: Ein Beitrag zur klimamorphologischen Zonierung der Erde - Hempel, Ludwig (ERDKUNDE, 1958)
The following values of geomorphological altitudinal limits for the northern flank of the Sierra Geomorphological Altitudinal Limits in the Spanish Sierra Nevada have been calculated. Whilst the climatic snow line is now at above 3,500 m., during the late glacial period its highest position was 3,200 m. and its lowest 2,850 m. During the Würm glacial period it lay at 2,400-2,500 m., during earlier glacial periods at 2,000-2,200 m. The pre sent lower limit of solifluction is at 2,100 m., its upper limit above 3,500 m.; during the Pleistocene its maximum altitude was at 800-1,000 m., its upper limit is not ascertainable. These findings agree with other observations in the Mediterranean region, such as those of Büdel in southern Italy and Sicily and Poser in Crete. On the other hand they do not fit into the conjectured profiles of these limits from Europe to Africa which have been given so far. That illustrates the supposition that in the Mediterranean region, as elsewhere, the climate-morphological limits of the Holocene as well as the Pleistocene do not rise regularly.